Presentation Skills for Technical Professionals - NAOMI KARTEN (IT Governance Ltd, 2010)
This book is practical, pragmatic, and a joy to read: concise, clever, captivating and compelling. It allows you to settle down, focus, find your voice and confidence; it reminds you of the undisputable humanity of your audience, yourself, and all the other wary presenters who came before. It allows you to take pride and joy in the outcome. So free your fears, halve your heartache, unravel your uncertainties, and set your mind at ease. I can think of no better guide for a technical person seeking excellent presentation skills than Naomi Karten‘s Presentation Skills for Technical Professionals.